Understanding outcomes in family-based treatment for adolescent anorexia nervosa: a network approach. Issue 2 (6th January 2023) - Hagan, Kelsey E.; Matheson, Brittany E.; Datta, Nandini; L'Insalata, Alexa M.; Onipede, Z. Ayotola; Gorrell, Sasha; Mondal, Sangeeta; Bohon, Cara M.; Grange, Daniel Le; Lock, James D.
Abstract: Background: Family-based treatment (FBT) is the first-line treatment for adolescent anorexia nervosa (AN). Yet, remission is not achieved for about half of adolescents with AN receiving FBT. Understanding patient- and parent-level factors that predict FBT response may inform treatment development and improve outcomes. Methods: Network analysis was used to identify the most central symptoms of AN in adolescents who completed the Eating Disorder Examination (EDE) prior to FBT ( N = 409). Bridge pathways between adolescent AN and parental self-efficacy in facilitating their child's recovery from AN were identified in a subset of participants ( n = 184). Central and bridge symptoms were tested as predictors of early response (⩾2.4 kg weight gain by the fourth session of FBT) and end-of-treatment weight restoration [⩾95% expected body weight (EBW)] and full remission (⩾95% EBW and EDE score within 1 standard deviation of norms). Results: The most central symptoms of adolescent AN included desiring weight loss, dietary restraint, and feeling fat. These symptoms predicted early response, but not end-of-treatment outcomes. Bridge symptoms were parental beliefs about their responsibility to renourish their child, adolescent discomfort eating in front of others, and adolescent dietary restraint. Bridge symptoms predicted end-of-treatment weight restoration, but not early response nor full remission. Conclusions: Findings highlight the prognostic utility of core symptoms of adolescent AN. Parent beliefs about their responsibility to renourish their child may maintain associations between parental self-efficacy and AN psychopathology. These findings could inform strategies to adapt FBT and improve outcomes.